The protective effects of Pimavanserin against cerebral ischemia-induced brain injury. Issue 1 (1st January 2021) - Li, Xiang; Tian, Xiaoyan
ABSTRACT: The integrity of the blood-brain barrier (BBB) is mainly maintained by the brain vascular endothelial cells and the tight junctions amongst them. Pimavanserin is a novel agent approved for the treatment of Parkinson's disease and exerts neuroprotective properties. The present study aims to explore the possibility that Pimavanserin might be an effective agent used for the treatment of cerebral ischemia stroke. Middle cerebral artery occlusion (MCAO) was established in mice, and oxygen-glucose deprivation/reoxygenation (OGD/R) was established in brain bEND.3 endothelial cells. Mice were randomly divided into four groups: (1) Sham operation group; (2). Pimavanserin (1 mg/kg); (3). MCAO; (4). Pimavanserin+ MCAO. We found that compared to the Sham group, the elevated neurological deficit score and brain water content increased production of inflammatory factors, increased BBB permeability, and downregulated Claudin 5 expression were observed in the MCAO group and were all dramatically reversed by the administration of Pimavanserin. Brain bEND.3 endothelial cells were treated with Pimavanserin before the exposure to OGD/R. The significantly increased lactate dehydrogenase (LDH) release, declined cell viability, increased endothelial permeability, downregulated Claudin 5 and Krüppel-like factors 6 (KLF6) were observed in the OGD/R group and were all reversed by the introduction of Pimavanserin. Lastly, the effects of Pimavanserin on the expression level of Claudin 5 and endothelial permeability in OGD/R-challenged endothelial cells were both abolished by the knockdown of KLF6. Taken together, our data revealed that Pimavanserin protected against cerebral ischemia injury by regulating the BBB integrity in a KLF6-dependent manner.